Penanganan Sengketa Pertanahan dalam Perspektif Agraria - Bimo Ashidiq, Tri Okto; Silviana, Ana (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Dispute is an inseparable part of conflict, which can occur in various aspects of daily life. Studying disputes is crucial to understand their nature and resolution methods. This research uses a normative research method with prescriptive research specifications and a comparative, conceptual, and historical approach. Data is collected through a bibliographic study from primary, secondary, and tertiary legal sources. Land conflicts are often caused by issues such as boundary disputes, inheritance, state land control, and legal uncertainty in land tenure, which fundamentally stem from the imbalance of land rights ownership and uncontrolled land conversion. Land dispute resolution can be carried out through litigation and non-litigation pathways. The litigation pathway offers legal certainty, execution power, and transparency but has weaknesses in terms of cost, time, and its confrontational nature. Conversely, the non-litigation pathway is more efficient in terms of cost, time, and its collaborative nature, but is limited in terms of execution and legal certainty. Therefore, the choice of dispute resolution method must consider the characteristics of the dispute and the needs of the parties involved.